Evaluation of the Effects of Degradable Mulching Film on the Growth, Yield and Economic Benefit of Garlic - Jiangping Song; Huixia Jia; Yang Wang; Xiaohui Zhang; Wenlong Yang; Tingting Zhang; Naijian Wang; Jianqiang Yang; Haiping Wang (Agronomy)
Polyethylene mulch film (PEM) is widely utilized in garlic cultivation, significantly enhancing garlic yield. However, the prolonged use of this material leads to serious environmental issues that adversely affect soil health and plant growth. To promote the adoption of biodegradable mulch film (BDM) in garlic cultivation, we investigate the effects of BDMs with thicknesses of 0.006 mm, 0.008 mm, and 0.010 mm on garlic growth and soil properties, comparing them with the commonly used PEM 0.008 mm. The results indicated that the agronomic traits of garlic were significantly improved under both PEM and BDMs compared to no mulching, with yield increases ranging from 75.42% to 90.39%. The highest garlic yield was observed with the BDM 0.008 mm. Most above-ground agronomic traits of garlic did not exhibit significant differences between PEM and BDMs, although a few traits showed slight increases under the BDMs 0.008 mm and 0.010 mm. The quality characteristics of garlic bulbs, including the contents of soluble sugar, vitamin C, and allicin, did not differ significantly between PEM and BDMs. Soil temperature was significantly higher under both PEM and BDMs compared to no mulching. In comparison to PEM 0.008 mm, the application of BDMs 0.006 mm and 0.008 mm significantly enhanced potassium availability in the soil. Furthermore, the activities of catalase, phosphatase, and invertase were notably increased under the BDM 0.008 mm, suggesting that this type of mulch could improve the physicochemical properties of the soil. Additionally, the BDM 0.008 mm remained intact throughout the low-temperature overwintering period, began to partially degrade as temperatures rose in March and April, and exhibited considerable fragmentation during the maturity and harvest periods of garlic. Its degradation rate was well aligned with the growth requirements of garlic. Taken together, these findings suggested that the BDM 0.008 mm is particularly effective, resulting in significant yield increase and an appropriate degradation rate. These results provided a valuable reference for the selection and application of BDM in garlic cultivation.